2007
DOI: 10.1249/mss.0b013e3180335c3c
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Differences in Youth Physical Activity

Abstract: The observed age-related decline in adolescent boys and girls PA is antithetical to public health goals; as such, it is an important area of research. To fully understand gender disparities in PA, consideration must be given to the confounding effects of physical maturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
186
11
25

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(254 citation statements)
references
References 26 publications
32
186
11
25
Order By: Relevance
“…However, if this decline remains even if controlled by body fat, the cause can be attributed to external factors and not to biological variables. Evidence shows a decrease in physical activity levels with advancing sexual maturation stages (26,27) . This suggests that the reduced physical activity level observed in this phase of life (27) can be a factor that contributes to the low cardiorespiratory fitness levels found.…”
Section: Discussionmentioning
confidence: 99%
“…However, if this decline remains even if controlled by body fat, the cause can be attributed to external factors and not to biological variables. Evidence shows a decrease in physical activity levels with advancing sexual maturation stages (26,27) . This suggests that the reduced physical activity level observed in this phase of life (27) can be a factor that contributes to the low cardiorespiratory fitness levels found.…”
Section: Discussionmentioning
confidence: 99%
“…Given the small sample size of children participating in this study, the results may not accurately represent other children of this age. The small sample size also limited other analyses of other possible moderating factors such as weight status and gender that have been found significant in recently published studies examining objective physical activity (11,67,77). A second limitation was the use of the broad term of physically active games to assess psychosocial responses on the child questionnaire.…”
Section: Chapter 5 -Discussionmentioning
confidence: 99%
“…According to the ecological model of physical activity (Figure 2-1 Epidemiological studies on youth physical activity have consistently revealed that males are more active than females, [64][65][66][67] and that age is inversely associated with physical activity. 64,65,67,68 The declines throughout youth have been reported in both self-report and objective measure of physical activity.…”
Section: Determinants Of Physical Activity and Overweight/obesity Amomentioning
confidence: 99%
“…64,65,67,68 The declines throughout youth have been reported in both self-report and objective measure of physical activity. 64 The studies reported that the annual rate of decline is much greater during adolescence than during adulthood.…”
Section: Determinants Of Physical Activity and Overweight/obesity Amomentioning
confidence: 99%
See 1 more Smart Citation